SENTIMENT ANALYSIS OF CUSTOMER SATISFACTION IN GOJEK AND GRAB APPLICATION REVIEWS USING THE NAIVE BAYES ALGORITHM - Ananda, Ridha Faiz; Syahri, Alfi; Hasan, Firman Noor (Jurnal Teknik Informatika (Jutif), 2024)
Online motorcycle taxis are a widely favored mode of public transportation in Indonesia. There are several companies providing online motorcycle taxi services in Indonesia, with Gojek and Grab dominating the market. In this rapidly digitizing era, social media has become a platform for Indonesian citizens to express their evaluations and opinions. One common platform used by users to express their evaluations is the Google Play Store, where users can provide ratings and opinions on the applications they use, including users of Gojek and Grab applications.This research aims to understand and analyze the sentiments of the public towards the two dominant giants in the online motorcycle taxi market in Indonesia based on review data from the Google Play Store using the Naive Bayes algorithm. The data used consists of user reviews from May 14, 2023, to July 26, 2023, totaling 300 data points for each application. This data will undergo pre-processing to remove irrelevant elements. The Naive Bayes algorithm is used to classify the existing sentiments into two classes: positive and negative.The results of this research conclude that Gojek users give positive reviews at 49% and negative reviews at 51%, which include praises for the drivers and services provided by the company, complaints about the heaviness of the application, and some disruptions in the Gopay payment method. Meanwhile, Grab users give positive reviews at 67% and negative reviews at 33%, which include customer satisfaction with attractive promos, complaints about the heaviness of the application after the latest update, and the high cost of Grabexpress and Grabfood services.